ANALISIS RISIKO KESALAHAN PELAPORAN PAJAK PERTAMBAHAN NILAI DAN IMPLIKASINYA TERHADAP TAX PLANNING PERUSAHAAN - Bagas Arya Satya Dinata; Ardhi Islamuddin (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Errors in the reporting of Value Added Tax (VAT) remain a significant issue for companies, as they may lead to the amendment of VAT returns, fiscal corrections, administrative penalties, and reduced effectiveness of corporate tax planning. This study aims to analyze the risks associated with VAT reporting errors, identify their underlying causes, and examine their implications for the implementation of corporate tax planning. The research adopts a qualitative approach using a case study design involving one of the clients of KAP XYZ. Data were collected through semi-structured interviews, direct observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and methodological triangulation. The findings indicate that the risk of VAT reporting errors is primarily driven by human error, delays in receiving tax invoices from vendors, discrepancies between accounting records and tax data, and the high volume of business transactions. During the study period, the company submitted 19 amendments to its monthly VAT returns, resulting in changes to its overpaid VAT position, which subsequently served as the basis for carrying forward tax credits to the following tax periods as part of the company's cash flow management strategy. Nevertheless, the company's Effective Tax Rate (ETR) was recorded at 21.98%, closely aligning with Indonesia's 22% corporate income tax rate, indicating that the company generally fulfilled its tax obligations in compliance with prevailing tax regulations. The study concludes that strengthening internal controls, conducting periodic data reconciliation, optimizing the utilization of the Coretax system, and implementing regular tax reviews are essential strategies for minimizing the risk of VAT reporting errors while enhancing the effectiveness of corporate tax planning